The early letters of Bishop Richard Hurd, 1739-1762 - Hurd, Richard 1720-1808 (Boydell & Brewer, 1995)
Richard Hurd is best known to ecclesiastical historians as one of George III's favourite bishops who was offered, and declined, the archbishopric of Canterbury. These letters, therefore, illuminate the early career of one of the most prominent clerics of the late eighteenth century. The letters begin in 1739, just after Hurd had graduated B.A. at Emmanuel College, Cambridge. They chart his gradual climb up the ladder of ecclesiastical preferment, through his time as Fellow at Emmanuel and end with him settled in the comfortable country rectory of Thurcaston in Leicestershire. Hurd had a wide circle of correspondents. He became a close friend of William Warburton, Bishop of Gloucester, perhaps the most prominent controverialist of the period. He was also a member of a literary circle which included the poets Thomas Gray and William Mason. Indeed, Hurd himself is well-known to students of English literature as the author of Letters on Chivalry and Romance and as a significant figure among the so-called 'pre-romantics'. Hurd's letters reveal the full range of his interests, from theology and university politics, through literature, to painting and sculpture. This edition, therefore, not only tells us about Hurd's early life and career, but also provides a valuable insight into the social life of the Anglican clergy in the eighteenth century
Title from publisher's bibliographic system (viewed on 18 Sep 2018)
Keywords: Hurd, Richard / 1720-1808 / Correspondence; Church of England / England / Clergy / Correspondence; Authors, English / 18th century / Correspondence; England / Intellectual life / 18th century